MAKNA KEPERCAYAAN KONSUMEN E-COMMERCE PERSPEKTIF EKONOMI ISLAM: STUDI FENOMENOLOGI KARANG TARUNA BOJONGSARI - Wulan Rindyana Syafitri; Jaharuddin Jaharuddin (Taksasila Edukasi Insani, 2026)
The rapid growth of e-commerce has significantly increased digital transactions across various segments of society, including young Muslim consumers. However, previous studies have generally emphasized consumer trust in technical aspects such as ratings, product quality, and platform security, while limited attention has been given to the meaning of trust from the perspective of Islamic economics. This study aims to analyze the meaning of consumer trust in e-commerce transactions based on the perspective of Islamic economics. This research employed a qualitative approach using a phenomenological method. The participants consisted of eight informants selected purposively, including seven members of Karang Taruna Bojongsari as the main informants and one business owner as the key informant. Data were collected through in-depth interviews and analyzed using thematic analysis assisted by NVivo 14 software. The findings reveal that consumer trust is not formed instantly, but develops through transaction experiences, social interactions, and evaluations of sellers’ ethical behavior. Values such as honesty, trustworthiness (amanah), transparency, and product halalness were found to be important factors in strengthening Muslim consumers’ trust. This study confirms that the implementation of Islamic economic values in e-commerce practices contributes to the creation of a more ethical and sustainable digital trade ecosystem.Keywords: Consumer trust, e-commerce, Islamic economics, amanah, phenomenology